Accidental heroes [compact disc, unabridged] : a novel - Steel, Danielle (Recorded Books, LLC, 2018)
A decorated former Air Force pilot. A pregnant flight attendant. A dedicated TSA agent. The fates of these three, and many others, converge as ordinary men and women in fight for their lives during a flight from New York to San Francisco.